Contrasting effects of soil microbial interactions on growth–defence relationships between early‐ and mid‐successional plant communities. Issue 3 (19th August 2021) - Geisen, Stefan; Heinen, Robin; Andreou, Elena; van Lent, Teun; ten Hooven, Freddy C.; Thakur, Madhav P.
Summary: Plants allocate resources to processes related to growth and enemy defence. Simultaneously, they interact with complex soil microbiomes that also affect plant performance. While the influence of individual microbial groups on single plants is increasingly studied, effects of microbial interactions on growth, defence and growth–defence relationships remain unknown, especially at the plant community level. We investigated how three microbial groups (bacteria, fungi, protists), alone and in full‐factorial combinations, affect plant performance and potential growth–defence relationships by measuring phenolics composition in early‐ and mid‐successional grass and forb communities in a glasshouse experiment. Microbial groups did not affect plant growth and only fungi increased defence compounds in early‐ and mid‐successional forbs, while grasses were not affected. Shoot biomass–defence relationships were negatively correlated in most microbial treatments in early‐successional forbs, but positively in several microbial treatments in mid‐successional forbs. The growth–defence relationship was generally negative in early‐successional but not in mid‐successional grasses. The presence of different microbiomes commonly removed the observed growth–defence relationships. We conclude that soil microorganisms and their interactions can shift growth–defence relationships differentially for plant functional groups and the relationships vary between successional stages. Microbial interaction‐induced growth–defence shifts might therefore underlie distinct plant strategies and fitness. Abstract : See also the Commentary on this article by Bender, 233 : 1015–1017 .